Synthesis of 2-phenyl imino-3-substituted phenyl-5-(ω-methoxy carbonyl heptyl)-4-thiazolidinone. - SOLANKEE, ANJANI; KAPADIA, KISHOR (Asian Journal of Chemistry, 2010)
2-Phenyl imino-3-substituted phenyl-5-(ω-methoxy carbonyl heptyl)-4-thiazolidinones have been synthesised by the treatment of thionyl chloride and methanol on 2-phenyl imino-3-substituted pheny 1-5-( ω-carboxy heptyl)-4-thiazolidinones.